Tandem Cu/ZnO/ZrO2‑SAPO-34 System for Dimethyl Ether Synthesis from CO2 and H2: Catalyst Optimization, Techno-Economic, and Carbon-Footprint Analyses - Mangalindan, Jasan Robey; Mahnaz, Fatima; Vito, Jenna; Suphavilai, Navaporn; Shetty, Manish (ACS Engineering Au, 2025)
To alleviate detrimental effects associated with anthropogenic emissions, the use of CO2 and H2 as feedstocks for their conversion to dimethyl ether (DME) with tandem catalysts is an attractive and sustainable route. First, we investigated the catalytic activity of bifunctional admixtures of Cu-ZnO-ZrO2 (CZZ) and a silicoaluminophosphate, SAPO-34, for CO2 hydrogenation to DME and optimized their reactivity with an emphasis on identifying optimum synthesis conditions for CZZ including Cu:Zn:Zr molar ratio and aging and calcination temperatures. The highest methanol (MeOH) productivity (10.8 mol kgcat –1 h–1) was observed for CZZ-611 aged at 40 °C and calcined at 500 °C. When coupled with SAPO-34, CZZ/SAPO-34 reached 20% CO2 conversion and 56% DME selectivity at optimized conditions (260 °C, 500 psig, and 2000 mL gCZZ –1 h–1) and was stable for 50 h time-on-stream, with a slight reduction in activity. Next, we performed kinetic modeling to translate lab-scale findings to industrial packed-bed reactors followed by a techno-economic analysis (TEA) with cradle-to-gate environmental footprint evaluation to evaluate its industrial applicability. A TEA of a 20,000 tpy DME plant revealed raw material costs as the main operating cost drivers (H2 cost comprises 47% of total cost). Considering green H2 ($4/kg H2) and captured CO2 as feed, the minimum DME selling price (MDSP) was $3.21/kg, ∼2.7× higher than the market price ($1.2/kg). MDSP drops to $1.99/kg with gray H2 ($1/kg H2) and fluctuates ±$0.14 with changes in CAPEX (±30%) and other economic factors. The plant’s carbon footprint was mainly affected by the H2 source. Green and gray H2 resulted in emissions of 0.21 and 4.4 kg CO2 eq/kg DME, respectively. Importantly, a negative carbon footprint can be achieved by using green H2 and CO2 captured directly from air. Overall, our work shows tandem catalysis as a promising approach toward sustainable DME production and identifies the pathway toward making it cost-competitive with fossil fuels.